1998
DOI: 10.1007/s004280050154
|View full text |Cite
|
Sign up to set email alerts
|

A pancreatic mucinous cystadenoma in a man with mesenchymal stroma, expressing oestrogen and progesterone receptors

Abstract: A 43-year-old man presented with abdominal discomfort caused by relapsing pancreatitis. Radiological examination revealed a multilocular cystic mass in the tail of the pancreas, which was resected. Gross examination showed a multilocular cystic lesion measuring 2.5 cm in diameter and containing clear fluid. Microscopically, a mucinous cystadenoma with mesenchymal stroma was diagnosed. The lesion showed two different components: a cyst lined by a columnar, mucin-secreting epithelium and a moderate cellular stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 10 publications
2
31
3
Order By: Relevance
“…Immunohistochemical staining for estrogen and progesterone receptor was not routinely performed in our study if OS was clearly evident from microscopical examination. The description of a male patient with cystadenoma of the pancreas containing stromata that expressed estrogen and progesterone receptors is remarkable [14]. To our knowledge, the presence of mucinous cystadenoma with OS in the spleen has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical staining for estrogen and progesterone receptor was not routinely performed in our study if OS was clearly evident from microscopical examination. The description of a male patient with cystadenoma of the pancreas containing stromata that expressed estrogen and progesterone receptors is remarkable [14]. To our knowledge, the presence of mucinous cystadenoma with OS in the spleen has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 56 MCN defi ned strictly by presence of ovarian stroma, 9 patients (16%) were 1 60 years of age [28] . Also, there are male patients with mucinous cystadenoma with ovarian-type stroma [28,31] .…”
Section: C Should Ovarian-type Stroma Be a Histological Requirementmentioning
confidence: 99%
“…The higher frequencies that have been reported in some previous studies are probably due to the fact that IPMNs and MCNs were not clearly distinguished from each other or were still interpreted as a single entity. The clear differentiation of MCNs from IPMNs also revealed that MCNs are extremely rare in men [31,37]. The mean age at diagnosis is usually below 50 years (table 3), though patients with invasive carcinoma are often older than 50 years.…”
Section: Mucinous Cystic Neoplasmmentioning
confidence: 99%